Audit Challenges: Dilemmas for the Auditor in a Global Economy - Karen A Van Peursem (Asian Academy of Management Journal of Accounting and Finance, 2005)
This paper is a market-informed analysis of the pressures that come to bear on the auditor of corporate accounts. It is argued that the integrity and independence of the auditor is a portion of the service quality which they bring to the exercise of providing an audit opinion. An economic model is then brought into play in order to illustrate how meeting public expectations, meeting the competitive environment, pleasing the client-company and fulfilling the appearance of independence with practice create pressures on the auditor to produce an 'opinion' that is less than independently-informed. The paper concludes with recommendations for action that may provide greater economic incentives for the auditor to conduct an ethical audit.